Doping Strategies for Promising Matel Halide Perovskite Based Solar Cells - Feng, Yuhan (Transactions on Computer Science and Intelligent Systems Research, 2025)
The metal halide perovskites have been broadly utilized as key materials in the development of solar cells due to their outstanding optoelectronic advantages. However, several challenges remain, including poor stability under high temperatures and humid conditions, the toxicity associated with lead at the B-site, and initial efficiency losses caused by ion migration. To address these issues, researchers have explored ion doping at various lattice sites. This paper first introduces the crystal structure of metal halide perovskites and highlights the advantages of perovskite-based solar cells. It then summarizes recent progress in ion doping at the A- and B-site, focusing on its impact on optoelectronic performance and the stability of perovskite solar cells. In the future, targeted doping at the A-site and B-site is expected to remain a crucial strategy for enhancing the performance and reliability of metal halide perovskite-based solar cells.